Improving the quality of soluble dietary fiber from Poria cocos peel residue following steam explosion - Tianlin Wang; Zhongshan Xiao; Tiange Li; Ge Guo; Suyun Chen; Xianqing Huang (Food Chemistry: X, 2023)
Poria cocos peel residue (PCPR) still contains much soluble dietary fiber (SDF), steam explosion (SE) treatment was applied to PCPR to create a superior SDF. Steam pressure of 1.2 MPa, residence period of 120 s, and moisture content of 13% were the optimized parameters for SE treatment of PCPR. Under optimized circumstances, SE treatment of PCPR enhanced its SDF yield from 5.24% to 23.86%. Compared to the original SDF, the SE-treated SDF displayed improved enzyme inhibition, including the inhibition of α-amylase and pancreatic lipase, also enhanced water holding, oil holding, water swelling, nutrient adsorption including cholesterol, nitrite ions, and glucose and antioxidant abilities. Additionally, it had a decreased molecular weight, improved thermal stability, and a rough surface with many pores of different sizes. Given that SDF had been improved physiochemical and functional characteristics thanks to SE treatment, it might be the excellent functional ingredient for the food business.